Subacute Sclerosing Panencephalltis: Clinical and Laboratory Manifestations - Hardiono D. Pusponegoro; Jimmy Passat; M. Hardjono Abdoerachman (Indonesian Pediatric Society, 1992)
We reviewed clinical and laboratory findings of 12 cases of Subacute sclerosing panencephalitis (SSPE) hospitalized at our department from 1985 to 1991. All cases were diagnosed and hospitalized at the 2nd stage. The principal clinical manifestations were mental changes, myoclonus, and frequent falls. Other clinical manifestations were ocular changes, involuntary movements, loss of social contact, and spasticity. Diagnosis was based on suppression-burst pattern in EEG and positive antibody titer to measles in serum and cerebrospinal fluid. CT scan was not diagnotic, since it was either normal or showed only non-specific cortical atrophy. Eleven patients (91, 7%) recalled a history of measles in the past. Age of onset of SSPE varied among cases and was difficult to specify precisely due to its subtle nature. None of the cases had been vaccinated against measles. SSPE is a rare disease, but is almost always fatal with prolonged suffering of the patient. Based on our experience with SSPE patients, we recommend to broaden the immunization programme against measles.